Controlling factors and dynamical formation models of lacustrine organic matter accumulation for the Jurassic Da'anzhai Member in the central Sichuan Basin, southwestern China. (September 2017) - Xu, Qilu; Liu, Bo; Ma, Yongsheng; Song, Xinmin; Wang, Yongjun; Xin, Xiankang; Chen, Zhangxin
Abstract: The lacustrine shale in the Jurassic Da'anzhai Member is considered as an excellent source rock in the central Sichuan Basin. However, geochemical studies of lacustrine organic matter (OM) accumulation factors and mechanisms are scarce. This study investigated the variations in total organic carbon (TOC), major elements, trace elements (TEs), and δ 13 C and δ 18 O values to reconstruct the paleoenvironmental conditions, biotic productivity, terrestrial inputs and other factors to improve the understanding of the controlling factors and dynamical formation models for lacustrine OM. The target shale was deposited in a fluctuating and complicated terrestrial open lake that exhibited oxic-suboxic oxygen levels, weak to moderate hydrodynamic conditions, a dry to humid climate, moderate weathering, and fresh to saline water conditions. The lake experienced moderate-high biotic productivity under a warm, humid climate and featured abundant flora and fauna. Compared to the Da1 3 shale, the Da1 shale featured higher salinity levels, a hotter and drier climate, greater weathering and more reduced conditions. The Da1 3 shale experienced stronger hydrodynamic forces and a more humid climate. Moreover, the TOC values of the Da1 3 correlate better with the indicators of redox conditions and exhibit little or no correlation with indicators of climate, weathering, salinity and biotic productivity, indicating that the lacustrine OM was mainly controlled by the redox conditions. Additionally, factors such as hydrodynamic conditions and terrestrial inputs exerted some degree of influence. Based on these factors and their relationships, two dynamical formation models are proposed: a high-salinity low-oxygen dynamical formation model (Model I) and a deep-water low-oxygen dynamical formation model (Model II). Model I stresses that the low oxygen levels were mainly caused by salinity, whereas Model II stresses that the low oxygen levels were mainly caused by deep depth. Both models can be classified as preservation models. Highlights: An accumulation of lacustrine organic matter was studied using geochemical methods. Lacustrine paleo-conditions, biotic productivity and terrestrial inputs were studied. Redox conditions played a dominant role in the preservation of the organic matter. A high-salinity low-oxygen model and a deep-water low-oxygen model were proposed. The lacustrine organic matter accumulation is best explained by preservation models.